Markovian Demands on Two Commodity Inventory System with Queue-Dependent Services and an Optional Retrial Facility - K. Jeganathan; M. Abdul Reiyas; S. Selvakumar; N. Anbazhagan; S. Amutha; Gyanendra Prasad Joshi; Duckjoong Jeon; Changho Seo (Mathematics, 2022)
The use of a Markovian inventory system is a critical part of inventory management. The purpose of this study is to examine the demand for two commodities in a Markovian inventory system, one of which is designated as a major item (Commodity-I) and the other as a complimentary item (Commodity-II). Demand arrives according to a Poisson process, and service time is exponential at a queue-dependent rate. We investigate a strategy of <semantics>(s,Q)</semantics> type control for commodity-I with a random lead time but instantaneous replenishment for commodity-II. If the waiting hall reaches its maximum capacity of N, any arriving primary client may enter an infinite capacity orbit with a specified ratio. For orbiting consumers, the classical retrial policy is used. In a steady-state setting, the joint probability distributions for commodities and the number of demands in the queue and the orbit, are derived. From this, we derive a waiting time analysis and a variety of system performance metrics in the steady-state. Additionally, the physical properties of various performance measures are evaluated using various numerical assumptions associated with diverse stochastic behaviours.